Nature of foulants and fouling mechanism in the Protein A MabSelect resin cycled in a monoclonal antibody purification process. Issue 1 (18th October 2015) - Zhang, Shaojie; Daniels, William; Salm, Jeffrey; Glynn, Judy; Martin, Joseph; Gallo, Christopher; Godavarti, Ranga; Carta, Giorgio
ABSTRACT: The composition and origin of foulants and their spatial distribution within the particles of the Protein A MabSelect resin cycled in a mAb purification process are determined using electron and confocal microscopy techniques with gold and fluorescently labeled protein probes that associate with the foulants. The results show that the foulants are primarily related to the mAb product, are heterogeneously dispersed both on the outer surface and in the interior of the resin beads, and accumulate only when loading the conditioned CHO cell culture supernatant. Insignificant accumulation is seen if the process is run with purified mAb or with the null cell culture supernatant. When bound to the Protein A ligand, the mAb responsible for the observed fouling behavior is shown to associate with BSA and α‐lactalbumin. This property is exploited using labeled versions of these lipophilic proteins to assess the effectiveness of improved resin cleaning processes and to elucidate the fouling mechanism. Resin fouling for this mAb appears to be consistent with the occurrence of conformational changes that occur upon binding, which, in turn, facilitate association of lipophilic proteins with the mAb. Upon desorption at low pH, these destabilized mAb complexes are deposited on and within the resin growing with each cycle and eventually leading to significant degradation of process performance. Biotechnol. Bioeng. 2016;113: 141–149. © 2015 Wiley Periodicals, Inc. Abstract : Proposed fouling mechanism of MabSelect resin by mAb A. When the mAb molecules bind to the Protein A ligands, a fraction of the mAb molecules undergo a conformational change, which exposes the hydrophobic patches at the surface of mAb molecules. Lipophilic proteins associate with these mAb molecules. During elution, most of these complexes are detached from the Protein A ligand in part refolding to the native form and in part precipitating out on and within the resin under the combined conditions of low pH and high local concentration. Once formed, unless removed by aggressive cleaning, these precipitates continue to grow as a result of cycling.